2018
DOI: 10.1038/s41550-018-0569-y
|View full text |Cite
|
Sign up to set email alerts
|

Observational signatures of massive black hole formation in the early Universe

Abstract: We study a simulation of a nascent massive, so-called direct-collapse, black hole that induces a wave of nearby massive metal-free star formation, unique to this seeding scenario and to very high redshifts. We implement a dynamic, fully-three dimensional prescription for black hole radiative feedback, star formation, and radiative transfer to explore the observational signatures of the massive black hole hosting galaxy. We find a series of distinct colors and emission line strengths, dependent on the relative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Lately, Barrow et al (2018) have suggested observational features of DCBH, claiming that the upcoming JWST telescope might be able to detect and distinguish a young galaxy that hosts a DCBH at z ∼ 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Barrow et al (2018) have suggested observational features of DCBH, claiming that the upcoming JWST telescope might be able to detect and distinguish a young galaxy that hosts a DCBH at z ∼ 15.…”
Section: Discussionmentioning
confidence: 99%
“…Popular analytical models require a number of hypotheses to allow the gas to collapse without fragmenting (see e.g. Bromm & Loeb 2003;Begelman et al 2006;Mayer et al 2010;Visbal et al 2014;Choi et al 2015;Valiante et al 2016Valiante et al , 2017Regan et al 2017;Barrow, Aykutalp, & Wise 2018;Chon, Hosokawa, & Yoshida 2018, for details and reviews).…”
Section: Selection Criteria For Dcbh Host Candidatesmentioning
confidence: 99%
“…Finally, first JWST and then a Lynx-like mission in the X-ray, should each be sensitive to ∼ 10 5 MBH black holes even at z ≈ 10 (e.g., Barrow et al 2018. The challenge will be identifying such accreting low-mass black holes, which will require extensive multi-wavelength data.…”
Section: Next-generation Opportunitiesmentioning
confidence: 99%
“…Previous studies have shown that Pop III SMSs with masses similar to those in our models would have extremely large luminosities that could be detected in the near infrared (NIR) by the James Webb Space Telescope (JWST) and large ground-based telescopes in the coming decade (Hosokawa et al 2013;Surace et al 2018Surace et al , 2019Whalen et al 2020b). Their BHs could also be found in the NIR at z ∼ 15 − 20 by JWST (Pacucci et al 2015;Natarajan et al 2017;Barrow et al 2018;Whalen et al 2020a) and at z ∼ 6 -8 by Euclid and the Roman Space Telescope (although lensing by galaxy clusters and massive galaxies in their wide fields could extend these detections up to z 10 -15; Vikaeus et al 2021). DCBHs will only be marginally visible to the Square Kilometre Array or next-generation Very Large Array in the radio at z 6 -8 (Whalen et al 2020b) but would become more luminous after growing to larger masses at later times.…”
Section: Discussionmentioning
confidence: 98%